Symphony no. 3 [compact disc] ; Three Latin American sketches - Copland, Aaron, 1900-1990 (American classics (Naxos (Sound recording label)), 2017)
Premiered in 1946, a year after the end of World War II, Copland's iconic Third Symphony was described by the composer as 'a wartime piece, or, more accurately, an end-of-war piece, intended to reflect the euphoric spirit of the country at the time'. Copland described the Three Latin American Sketches 'as being just what the title says. The tunes, the rhythms and the temperament of the pieces are folksy, while the orchestration is bright and snappy and the music sizzles along'.